The mediating role of brand image in the influence of influencer credibility and E-WoM on repurchase intention of skincare products in Denpasar City - Damariyanti, Komang Listia; Suprapti, Ni Wayan Sri (International research journal of management, IT and social sciences, 2025)
The increasing awareness among women regarding the importance of appearance and self-image, especially in the professional world, has driven the use of skincare products as part of personal branding and professionalism strategies. This study aims to examine the influence of influencer credibility and e-WOM on repurchase intention of skincare products, both directly and through the mediation of brand image. It also seeks to identify differences in repurchase intention between the two skincare brands. As the population is considered infinite, sampling was conducted using a non-probability sampling method with purposive sampling technique. A total of 150 respondents were selected based on specific criteria. T The results show that influencer credibility has no significant effect on repurchase intention or brand image. Meanwhile, e-WOM has a positive and significant effect on both variables. Brand image plays a crucial role in increasing repurchase intention and partially mediates the relationship between e-WOM and repurchase intention, but does not mediate the relationship between influencer credibility and repurchase intention. There is no significant difference in repurchase intention between Wardah and Skintific users. These findings highlight the important role of consumer reviews in shaping perception and repurchase intention in the skincare industry.